Diseminasi Agroteknologi melalui Vertical Garden dalam Mewujudkan Program Adiwiyata di SMA Negeri 13 Padang - Netti Herawati; Sanna Paija Hasibuan; Elara Resigia; Zulfadly Syarif; Teguh Budi Prasetyo (Warta Pengabdian Andalas)
SMA Negeri 13 Padang is one of the high schools in Padang, which has been the partner of the Faculty of Agriculture, Andalas University. Currently, the school is experiencing difficulties in developing the Adiwiyata program. The less than optimal use of the schoolyard becomes an obstacle in realizing this program. The vertical garden is a solution that can be applied in schools so that the yard's utilization can be done optimally. This activity aims to provide knowledge and understanding of the school regarding the vertical garden. This activity was carried out at SMA Negeri 13 Padang using survey methods, counseling, and demonstrations in making a vertical garden. Based on the activities carried out, the results obtained are 16% of the participants know about the vertical garden, and 84% of the participants do not learn the vertical garden technique yet. In the end of program, 80% of the participants understood the vertical garden technique and applied it in their respective classes. The knowledge and understanding of the participants increased by 64%.